Prinsip dan Etika Komunikasi dalam Penggunaan Media Baru - Aditya Eka Putra; Yohannes Don Bosco Doho; Galuh Ayu Savitri; Latif Fianto (Universitas Merdeka Malang, 2023)
This research aims to describe communication principles and ethics in the use of new media. Currently, in the digital era and increasingly advanced technological developments, it has an impact on all people's lives which have now shifted and become dependent on the use of new media. The qualitative descriptive method was carried out using interview, FGD and documentation data collection techniques. Next, data analysis was carried out using Miles and Huberman analysis starting from data collection, display, verification and conclusion. The results of the research show that communication ethics is very necessary for every human being, where someone's polite and/or impolite ethics can be seen from the way they communicate with other people, not only directly in the real world but also in the virtual world. In this article, the author finds several phenomena and cases to prove how important communication principles and ethics are in the use of new media.